DESCRIPTION OF THE INCIDENT OF ANEMIA IN ADOLESCENT WOMEN IN NAMORIH VILLAGE - Wahyuni, Dewi Sri; Susanti, Nofi; Siregar, Findyani; Syaharani, Latifah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Anemia is a global health issue that is particularly common in underdeveloped nations, where it affects about 30% of the population. In Namori Village, anemia is an illness that frequently affects young women. The purpose of this study is to determine how common anemia is among teenage girls in Namori Village in 2023. In this study, cross-sectional research methodology and quantitative analysis were used concurrently to collect data. From the Namorih Village Community, thirty research samples were gathered. Secondary data collection, or data gathered by researchers from pre-existing sources, is the methodology employed in this study. This study set out to find out how common anemia was in Namori Village.